Precise tuning of the charge transfer kinetics and catalytic properties of MoS2 materials via electrochemical methods - Chia, Xinyi (2015)
MoS2 has become particularly popular for its catalytic properties towards the hydrogen evolution reaction (HER). It has been shown that the metallic 1T phase of MoS2, obtained by chemical exfoliation after lithium intercalation, possesses enhanced catalytic activity over the semiconducting 2H phase due to the improved conductivity properties which facilitate charge-transfer kinetics. Here we demonstrate a simple electrochemical method to precisely tune the electron-transfer kinetics as well as the catalytic properties of both exfoliated and bulk MoS2-based films. A controlled reductive or oxidative electrochemical treatment can alter the surface properties of the film with consequently improved or hampered electrochemical and catalytic properties compared to the untreated film. Density functional theory calculations were used to explain the electrochemical activation of MoS2. The electrochemical tuning of electrocatalytic properties of MoS2 opens the doors to scalable and facile tailoring of MoS2-based electrochemical devices.